2017
DOI: 10.13057/biodiv/d180203
|View full text |Cite
|
Sign up to set email alerts
|

The estimation of dynamical distribution of domesticated Burgo chicken population in Bengkulu coastal area, Indonesia

Abstract: Abstract. Putranto HD, Hasibuan GP, Yumiati Y, Setianto J, Brata B, Kurniati N, Hakiki FF. 2017 Bengkulu coastal area, . The estimation of dynamical distribution of domesticated Burgo chicken population in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 2 publications
1
8
0
6
Order By: Relevance
“…By this sex ratio, we can also interpret that among bird keepers in Bengkulu City if there are 2 male birds that are kept then we can find 1 female that is maintained. Putranto et al (2017) found a similar pattern among burgo fanciers in Bengkulu who prefer to have male rather than female chicken. In case of White-rumped Shama birds, less number of female birds are kept in Bengkulu City caused by reason of male bird has a beautiful chirping and more expensive than female birds.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…By this sex ratio, we can also interpret that among bird keepers in Bengkulu City if there are 2 male birds that are kept then we can find 1 female that is maintained. Putranto et al (2017) found a similar pattern among burgo fanciers in Bengkulu who prefer to have male rather than female chicken. In case of White-rumped Shama birds, less number of female birds are kept in Bengkulu City caused by reason of male bird has a beautiful chirping and more expensive than female birds.…”
Section: Discussionsupporting
confidence: 58%
“…Bird population data were analyzed by using population density formula and population distribution formula (Putranto et al 2017), while profile of keepers was analyzed descriptively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spesies hewan yang berpotensi untuk dikembangkan sebagai ternak unggas lokal di Pulau Sumatera adalah ayam Burgo (Putranto et al, 2018;Setianto et al, 2019). Ayam Burgo yang selanjutnya disebut dengan Burgo atau Berugo merupakan ayam atau unggas eksotik dan endemik di Provinsi Bengkulu (Putranto et al, 2018(Putranto et al, , 2017(Putranto et al, , 2016(Putranto et al, , 2012aPutranto, 2011;Setianto et al, 2019). Bahkan dalam rangka menyongsong kegiatan Wonderful Bengkulu 2020, Pemerintah Provinsi Bengkulu telah menetapkan ayam Burgo atau Berugo atau Brugo sebagai salah satu ikon kegiatan berdampingan dengan ikon bunga Raflesia (Anonim, 2019).…”
Section: Pendahuluanunclassified
“…Informasi biologi yang telah diketahui antara lain DNA mitokondria ayam Burgo (Putranto et al, 2012a), hormon reproduksi betina dan sel telur (Putranto et al, 2012b) serta ukuran morfometriknya (Handika, 2018;Putranto et al, 2018). Sehubungan dengan kegiatan konservasi dan studi populasi maka telah pernah dipelajari tentang populasi ayam Burgo kelamin campuran (Putranto et al, 2010) serta populasinya pada daerah pesisir Bengkulu dengan aplikasi perangkat lunak sederhana (Putranto et al, 2017). Akan tetapi ternyata data tentang perilaku pada ayam Burgo jantan dan betina sampai saat ini masih belum banyak diketahui.…”
Section: Pendahuluanunclassified